The sequence matters: Expert opinions on policy mechanisms for bioenergy with carbon capture and storage - Lara-Sophie Wähling; Mathias Fridahl; Tobias Heimann; Christine Merk (Energy Research & Social Science, 2023)
This paper presents the results of a globally distributed survey on policies for incentivizing bioenergy with carbon capture and storage (BECCS). The current lack of policy incentives to support the implementation of BECCS constitutes a major deployment barrier. Therefore, scientists and policymakers are now debating the optimal BECCS policy framework. Previous studies have presented theoretical analyses of policy options to spur deployment, yet despite the considerable influence of experts on policy processes, very few studies have explored expert opinions. Drawing on an online survey of experts (N = 46), we explore their policy preferences and whether those preferences differ or converge between experts from different working sectors. The results show that a tax and refund scheme, a flat-rate subsidy, and reverse auctioning are considered more suitable than other measures. Furthermore, most experts agree that rather than a stand-alone policy, a policy mix would be needed in order to support BECCS deployment. Several experts propose a sequence of policies, moving from publicly funded supply-push policies in the short term to budget-neutral demand-pull policies in the longer term. Regarding various subsidy schemes, respondents favor investment subsidies or results-based subsidies based on stored biogenic carbon dioxide. The relatively minor differences in the response patterns between groups of experts suggest that a consensus on a preferred BECCS policy pathway might be forming across different sectors and interest groups. Therefore, our results could inform policymakers on policy instruments for BECCS that are considered most suitable by experts and thus help to shape the policy pathway for BECCS.
Keywords: 330; Bioenergy with carbon capture and storage (BECCS); Negative emissions; Net-zero; Policy instruments; Policy sequencing; Expert survey